Interspecific interference between Amaranthus hybridus L. and Amaranthus viridis L. - Maluf, Angela Maria (Pesquisa Agropecuaria Brasileira, 1999)
The objective of this paper was to study the interspecific interference between two Amaranthus species __ A. viridis e A. hybridus __, the latter with two distinct biotypes (green and purple); both species ocurred in two localities. In the populations of each of the locations, some independent substitution trials were made in pots, and it could be concluded that the populations that germinate more readily are those which are superior in competition i.e., those that establish themselves and produce the largest number of seeds. There was a tendency for A. hybridus (green biotype) to dominate both A. hybridus (purple biotype) and A. viridis, and for A. hybridus (purple biotype) to dominate A. viridis. In mixed stands, there were cases where the species were competing for the same resources, cases where they were exploiting different environmental resources, and even cases of mutual antagonism.